2017
DOI: 10.1007/s11356-017-8864-1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Legionella pneumophila positivity rate in hotel water samples from Antalya, Turkey

Abstract: The genus Legionella is a fastidious Gram-negative bacteria widely distributed in natural waters and man made water supply systems. Legionella pneumophila is the aetiological agent of approximately 90% of reported Legionellosis cases, and serogroup 1 is the most frequent cause of infections. Legionnaires' disease is often associated with travel and continues to be a public health concern at present. The correct water management quality practices and rapid methods for analyzing Legionella species in environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
3
7
0
1
Order By: Relevance
“…In Italy, the Lp sg1 distribution rates in the hotel setting differed greatly between two studies, at 27.7% and 55%, including mixed cultures [15,34]. On the other hand, findings from Italy [19], Greece [23], and Turkey [21] have shown that the most frequent colonizers of the hotel water systems in these studies were Lp sg2-14.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In Italy, the Lp sg1 distribution rates in the hotel setting differed greatly between two studies, at 27.7% and 55%, including mixed cultures [15,34]. On the other hand, findings from Italy [19], Greece [23], and Turkey [21] have shown that the most frequent colonizers of the hotel water systems in these studies were Lp sg2-14.…”
Section: Discussionmentioning
confidence: 67%
“…Several recent studies have focused on the prevalence and distribution of Legionella in water systems of hotels in non-outbreak situations. These studies revealed variable rates of contamination and species diversity [18][19][20][21], but limited data is published on the molecular diversity of Legionella spp. in hotel settings [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Akkaya et al [22] detected Legionella in 8 (6.7%) of the 120 samples taken from schools, hospitals, hotels and houses in Kayseri, Turkey, in 2008. Özen et al [23], in their study involving a total of 403 samples collected from 56 different hotels in Antalya, reported that L. pneumophila was isolated in 37.5% of the hotels and 10.1% of water samples. Ozen also reported that 85% of the samples were L. pneumophila serogroup 2-14 positive, and 15% of the samples were L. pneumophila serogroup 1 positive.…”
Section: Discussionmentioning
confidence: 99%
“…2010 yılında yapılan bir başka çalışmada ise, yine önemli turizm merkezlerinden bir ilde faaliyet gösteren 56 otelden alınan 1043 Legionella su örnekte analiz edilmiştir. Yirmi bir otelde ve 142 numunede (%10.1) Legionella üremesi belirlenmiştir (31) . Bir başka çalışmada, Ankara, İzmir, Tablo 3.…”
Section: Sudaunclassified